Correlation Between the Maturation Stages of Mandibular Third Molars and Chronological Age in Patients Visiting Sardar Begum Dental College, Peshawar - Muhammad Ilyas; Asma Khan; Syed Murad Ali Shah; Salman Khan; Junaid Nadeem Malik (Gandhara University, 2019)
OBJECTIVES: The objective of this study was to determine the correlation of chronological age with the maturation stages of mandibular third molar. METHODOLOGY: This descriptive, cross-sectional study was conducted at Sardar Begum Dental College, Gandhara University Peshawar on 384 patients from January 2018 to June 2018 and included patients having age 11-26 years with good quality Orthopantomogram showing mandibular third molar tooth germs bilaterally. Data were analyzed using SPSS version 22. p ≤ 0.05 was considered as statistically significant. RESULTS: Females 286 (74.5%) were predominant than males 98 (25.5%) with mean age presentation of 18.12±3.03 years. The most frequent stage of Demirjian's stages of mandibular third molar was stage F (24.7%). Pearson correlation showed that maturation stages of mandibular third molars were significantly related to the chronological age ( r=0.446, p value=0.00). CONCLUSION: A correlation between maturation stages of mandibular third molars and chronological age existed.